Perilaku pemilihan pakan plastik dan respons biologi imago kumbang Tenebrio molitor L. (Coleoptera: Tenebrionidae) - Choirul Mahdianto; Damayanti Buchori; Endang Sri Ratna (Jurnal Entomologi Indonesia, 2022)
The beetle Tenebrio molitor has potential as a plastic decomposer. Plastic can also be degraded by exposure to sunlight. The aim of this research was to determine the feeding behavior and biological responses of T. molitor exposed to various type of plastics. Seven types of plastics, namely bioplastics (Bio), expanded styrofoam (EPS), oxo-biodegradable (Oxo), three plastics Bio-P, EPS-P, Oxo-P that had been exposed to sunlight, and controls contained a mixed pollard-carrots slices were tested on four days-old of adult T. molitor. The choice feeding method was carried out at day and night by releasing 200 and 300 beetles in the middle of a ±15 cm diameter petri dish divided into 7 radial spaces, and their movement were observed within 24 hours. The forced feeding method for observing biological responses was carried out by releasing 10 male and female beetles in a petri dish as described above. The results showed that around 32–39% of the beetle population visited most of the pollard feed. In the feed treatment without pollard, 20% of the beetles chose EPS, EPS-P and Bio. Beetles survived 23 and 40 days on Bio and Bio-P feed, respectively. Egg production by the beetles exposed to the Bio and Bio-P diets was 2 and 3 eggs/female/10 days. Around 85% of pollard feed consumed contributed to 5% of body weight gain. About 58–64% of Bio, Bio-P, EPS, EPS-P and 6–12% Oxo, Oxo-P feeds were successfully consumed. The decrease in its body weight occurred in all plastic feed treatments ranging from 13–28%.